2021
DOI: 10.1002/ange.202100363
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic and Enantioselective Control of the C–N Stereogenic Axis via the Pictet–Spengler Reaction

Abstract: An unprecedented example of a chiral phosphoric acid‐catalyzed atroposelective Pictet–Spengler reaction of N‐arylindoles is reported. Highly enantioenriched N‐aryl‐tetrahydro‐β‐carbolines with C−N bond axial chirality are obtained via dynamic kinetic resolution. The hydrogen bond donor introduced on the bottom aromatic ring, forming a secondary interaction with the phosphoryl oxygen, is essential to achieving high enantioselectivity. A wide variety of substituents are tolerable with this transformation to prov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(5 citation statements)
references
References 80 publications
0
5
0
Order By: Relevance
“…Following this strategy, in 2021, Kwon and co-workers reported a similar process using N-aryl protected tryptamine derivatives 241 and (R)-BPA3 as the catalyst (Scheme 74). 213 In this case, a highly atroposelective reaction is described using paraformaldehyde and sterically hindered N-aryl groups. The intramolecular nucleophilic addition to formaldehyde-derived imine, again, limits the free-rotation of the N-aryl group, gener- ating axially-chiral heterocycles 242 in yields up to 99% and enantiomeric excesses up to 97%.…”
Section: Pictet-spengler Reactionmentioning
confidence: 99%
“…Following this strategy, in 2021, Kwon and co-workers reported a similar process using N-aryl protected tryptamine derivatives 241 and (R)-BPA3 as the catalyst (Scheme 74). 213 In this case, a highly atroposelective reaction is described using paraformaldehyde and sterically hindered N-aryl groups. The intramolecular nucleophilic addition to formaldehyde-derived imine, again, limits the free-rotation of the N-aryl group, gener- ating axially-chiral heterocycles 242 in yields up to 99% and enantiomeric excesses up to 97%.…”
Section: Pictet-spengler Reactionmentioning
confidence: 99%
“…Where additional comparison data is available, several other studies involving imine-type electrophiles (C=N-R) have shown the importance of including TCYP in a catalyst evaluation despite the structural similarities with TRIP. [32][33][34][35][36][37][38][39][40][41] By performing this type of analysis with similarly related electrophiles, azo compounds, [42][43][44][45][46] precedent shows TCYP to be a top performer. Continued expansion of this comparative analysis demonstrates TCYP to be effective in condensation, 47,48 halogenation [49][50][51][52] and organometallic reactions.…”
Section: Inverse Catalyst Designmentioning
confidence: 99%
“…In one category, functionalization of the peripheral groups in existing (hetero)aryl rings allows restriction of the C-N rotation by size-increasing effect. [15][16][17][18][19][20][21][22] Alternatively, de novo construction of a new (hetero)aryl ring with incorporatation of the C or N atom into it may also restrict the conformation of the C-N axis. The latter strategy is particularly important because new chiral platforms are constructed with modularity, which allows exploitation of diverse chiral structures.…”
Section: Chiral Ligands Have Also Been Demonstratedmentioning
confidence: 99%